The STRUGGLE FOR A BETTER LIFE IN DICKENS’ GREAT EXPECTATIONS - Amelia Gerung; Elisabeth Z Oroh; Merlin Maukar (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The research is intended to reveal Pip's struggle for a better life. He never gives up to reach his dream for better life as seen in Charles Dickens' Great Expectations. This research is categorized as a qualitative research because the data are taken in the form of words. The data are collected from primary source that is the novel itself, and the secondary sources are collected from some books, articles, internet and other sources that are used to support the analysis. In analyzing the data, the writer used objective approach. The result shows the struggle of Pip for a better life. The first struggles to be a gentleman, and the second struggles to get his love. Pip is an orphan and Pip always tries to be a gentleman so that his life can be better and he never gives up on getting Estella, the woman he loves. And in the end the efforts that Pip can do, Pip can get what he dreams of becoming a respectable man and getting Estella's love a woman he loves so much.